English vocabulary learning strategies of university students in Papua - Komari, Komari; Suryanto, Suryanto; Hanum, Upi Laila (Universitas Islam Negeri Banda Aceh, 2022)
This study investigated vocabulary learning strategies (VSL) used by university students in Papua and the relationship between VSL use and English learning achievement. It employed quantitative and qualitative approaches. Quantitative data was collected using Takač's questionnare of VLS and analysed by applying Oxford's Taxonomy of Language Learning Strategies (LLS). Three hundred and thirty-six students majoring in English department and non-English department participated in the questionnaire. Twelve students and six English teachers contributed their perspectives as qualitative data on the learning and teaching of vocabulary at their universities. Key findings included: memory strategies and compensation strategies were the most frequently used strategies; students majoring in English used a wider range of strategies and used them more frequently than did students majoring in other fields of study; high-achieving students used a wider range of strategies and used them more frequently than their low-achieving counterparts; the majority of students were interested in learning new vocabulary through games, songs, movies, role-plays, and using vocabulary cards; more emphasis on VLS instruction need to be placed.